Image Findings of Juxtacortical Lesions: A Review of Surface Bone Lesions. Issue 2 (13th April 2022) - Foremny, Gregory B.; Quintero, Daniel; Emerson, Christopher P.; Baker, Lauren; Subhawong, Ty; Pretell-Mazzini, Juan; Jose, Jean
Abstract : Juxtacortical lesions appear as neoplastic formations on the outer cortical surface of bone. They can arise from nonneoplastic and neoplastic origin, the latter of which might be malignant. Juxtacortical lesions of neoplastic origin can be categorized into bone-forming lesions, cartilaginous lesions, fibrous lesions, lesions of local vascular or neurogenic origin, or metastatic lesions. Forming a differential diagnosis can be challenging for any physician assistant. We selected a series of cases from our tertiary care clinic that have been subject to discussion for their similarity but vastly different prognosis. Our aim is to provide a rubric to compare juxtacortical lesions with guide orthopaedic and sport medicine providers in determining the immediacy of referral and follow-up.